Exploring student perceptions, learning outcome and gender differences in a flipped mathematics course. (14th April 2015) - Chen, So‐Chen; Yang, Stephen J.H.; Hsiao, Chia‐Chang
Abstract: The flipped classroom approach has recently gained prominence in education. However, a review of previous studies shows that the relationship associated with gender difference, student perceptions and learning outcomes has still remained unexplored, and there has been little discussion regarding flipped classroom environment. To fill this gap, this study aimed to provide a further study by developing an empirical study, extending perspectives of research for flipped classroom in education. This study was conducted to respond and investigate two main student perceptions in a flipped precalculus course, namely, situational interest and course satisfaction. By the self‐developed perception measures, situational interest contained feeling, value and topic interest (three factors), while course satisfaction contained course design, system quality, course arrangement and online assessment (four factors). To respectively determine factors on final grades, we assessed the predicting power among those factors. Students' feedback and gender differences were also evaluated to provide a holistic profile of this flipped course. Results showed that feelings predict the final grades in males, while course design predicts the final grades in females. Moreover, the result also showed that even if females and males showed different topic interest in this course, they performed equally well. Some suggestions to effectively implement a flipped course were also provided from students' feedback. The implications of the results were provided for instructors' guidance in implementing flipped classroom. Finally, the study concluded that students' perceptions may be considered as motivational strategies in teaching and learning process to involve students in academic activities for improving their grades in flipped course.